Peningkatan Reputasi Perusahaan Di Indonesia Melalui Sumber Pembiayaan Berbasis Green bond Dan Green sukuk - Endri Juniyanto; Atika Ulfah (Universitas La Tansa Mashiro, 2026)
The objective of this research is to empirically examine how financing through green bonds and green sukuk impacts the improvement of corporate reputation within Indonesia. Employing a quantitative methodology, this research utilizes secondary data extracted from the statistical reports of OJK and BEI over the 2019–2023 period. The sample selection technique was carried out using a purposive sampling method, resulting in a sample of 31 green bond series and 45 green sukuk series from various public companies. The data were analyzed using linear regression tests facilitated by the SEM-AMOS software. The findings indicate that both financing instruments yield a positive impact. Specifically, green bonds demonstrate a significant influence on corporate reputation (p < 0.027). Similarly, green sukuk also exhibit a substantial effect on corporate reputation, supported by a significance value of (<0.015).